NILAI-NILAI TASAWUF SEBAGAI FONDASI PENDIDIKAN KARAKTER PESERTA DIDIK DI ERA MODERN - Lailatul Aulia (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2026)
The modern era offers technological advancements yet simultaneously presents challenges to students’ character development, including increasing individualism, weakened self-control, and declining spiritual awareness. Sufism, as an integral part of Islamic intellectual tradition, provides moral and spiritual values that can serve as a strong basis for balanced character education. This study aims to explore Sufi values such as tazkiyatun nafs (purification of the soul), muhasabah (self-reflection), zuhd (simplicity), taqwa (piety), and mahabbah (love of God) as foundational principles for character development in modern educational contexts. Using a literature review method, this study analyzes classical and contemporary sources. The findings reveal that Sufi values are effective in fostering noble character, emotional self-regulation, and a balanced life orientation between worldly and spiritual goals. Therefore, Sufism remains relevant as a strategic approach in shaping students’ character amid the challenges of modernization.